Opposite effects of interleukin-4 and interleukin-10 on nitric oxide production in murine macrophages - Maru, A. (Hindawi Publishing Corporation, 1996)
Interleukin-4 (IL-4) and interleukin-10 (IL-10) were evaluated for their ability to inhibit the production of nitric oxide (NO) by interferon-γ (IFN-γ)- or lipopolysaccharide (LPS)-activated murine macrophages (RAW 264.7 and J774.2). Macrophages pre-treated with IL-4 and then stimulated with IFN-γ or LPS showed significant inhibition in their ability to produce NO as measured by nitrite production. Simultaneous treatment of IL-4 pre-incubated cells with IFN-γ and LPS together augmented nitrite accumulation. On the other hand, similar exposures of the macrophages to IL-10 followed by IFN-γ or LPS treatments resulted in significantly increased NO production. Thus IL-10 failed to suppress IFN-γ or LPS-induced NO production and showed opposite effects in these experiments to IL-4. We conclude that the two lymphokines have differing roles in the control of production of NO and might act to control the secretion of nitric oxide in vivo.